KEBERAGAMAN ETNIS MADURA DI KALIMANTAN BARAT - Iwan Ramadhan (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
This study aims to describe the diversity of the Madurese tribe in West Kalimantan, which is the pride and uniqueness of the Madurese tribe as well as the customs, traditions, and habits of the community based on the noble values of References and Guidelines. In this study, the authors adopted a library research method, namely, taking material related to the topic presented. The Madurese are a tribe who migrate a lot to areas far from their place of origin, and this aims to find a place to live or a livelihood that can better support their economic life. One of the areas where the Madurese migrate is the island of Kalimantan, in particular. West Kalimantan. The results of this study show how the diversity of the Madurese tribe in West Kalimantan starts from the arrival of the Madurese ethnic group in 1942-1950 who migrated from Bangkalan Madura, East Java, which brought salty things that are typical of Madura starting from the Madurese livelihood system, kinship system, traditional rituals start from eating red and white porridge (Tachin Mira Pote), molotan, bajemuk, and ashura porridge.